PERANAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL QUR’AN PADA SISWA KELAS VII SMPS SAFINATUSSALAMAH TAHUN PELAJARAN 2024/2025 - Muhammad Rosid Siregar; Afif Ansori; Mustaqim Hasan (UNISAN JURNAL, 2025)
This study aims to examine the role of Islamic Religious Education (IRE) teachers in improving the Qur’an reading skills of Grade VII students at SMPS Safinatussalamah in the academic year 2024/2025. The research employed a qualitative approach using observation, interviews, and documentation as data collection techniques. The findings reveal that IRE teachers play a strategic role in Qur’an reading instruction by applying various teaching methods such as the Iqra’ method, talaqqi, and direct instruction. Furthermore, teachers act as motivators and role models through their consistent religious behavior, which encourages students to emulate and engage actively in the learning process. Despite challenges such as limited family support and restricted instructional time, teachers successfully provide effective guidance and carry out continuous evaluations of students’ progress. The results show significant improvement in students’ fluency, correct pronunciation (makhraj), and application of tajweed rules. This research emphasizes the crucial role of teacher engagement and exemplary behavior in religious education, particularly in enhancing Qur’anic reading proficiency